The communicative management in social media of the emergence of Ebola in Spain - Percastre-Mendizábal, Salvador; Pont-Sorribes, Carles; Suau-Gomila, Guillem (Revista Española de Comunicación en Salud, 2019)
The Ebola crisis in Spain was a health crisis that took place in 2014. This crisis had political consequences such as the resignation of the former health minister of the Popular Party Government, Ana Mato, social as large mobilizations in different territories of the country, and humanitarian as the discussion regarding the contagion of the Spanish missionary Manuel García and that of the nursing assistant Teresa Romero; and there were even ethical debates surrounding the sacrifice of Teresa Romero’s mascot, Excalibur. The research aims to analyze to what extent and in what way administrations and the media used Twitter to communicate with citizens. Theoretically, it is based on the sociological field of risk and on the field of communication and journalism in digital environments. The methodology is mixed, and the research concluded that traditional media are still fundamental to communicate emergencies.